Uranium distribution and radon exhalation from Brazilian dimension stones - Amaral, P. G. Q. [UNESP]; Galembeck, T. M. B. [UNESP]; Bonotto, Daniel Marcos [UNESP]; Artur, A. C. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
This paper provides evaluations of the radiometric behavior and exhalation patterns of radon gas in decorative and dimension stones explored in the Brazilian states of Minas Gerais and Espirito Santo, given the importance of determining radon gas concentrations in human-inhabited environments. A total of 10 silicate rock types were studied, featuring different petrographic/petrophysical characteristics given by seven magmatic rocks (three of which are granitic pegmatites) and three metamorphic rocks. The study, comprising radiometric data of U and monitoring of Rn-222 gas exhalation, shows a strong correlation between petrographic parameters and the physical properties of rocks. U levels ranged between 2.9 and 37 ppm, revealing a good coherence between the presence and the absence of radioactive element-bearing accessory minerals for each rock type. The rate of radon exhalation from the stones is related to the petrographic/petrophysical features of each material. By comparing the Rn-222 level generated by a rock to the amount effectively emanated by it, the rate of emanated gas proves to be insignificant; also, a rock that produces more Rn will not always emanate more. Simulations performed to estimate the radon levels inside residences or any given indoor environment showed that nine samples attained values below the 4 pCi/L EPA limit, whereas one was above that limit. (c) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dimension stones; Radon exhalation; Indoor environment